F. Scott Fitzgerald - Bloom, Harold (Philadelphia : Chelsea House, 2002)
Examines the life and work of twentieth-century American author F. Scott Fitzgerald, featuring a biographical profile, critical analysis of the themes, symbols, and ideas in his writing, a selection of critical essays, a chronology, and references.
"Comprehensive biography and critical analysis"--Cover.
Includes bibliographical references (p. 119-121) and index.
Book Report.
Young Adult.
Young Adult
Keywords: Fitzgerald, F. Scott, -- 1896-1940 -- Criticism and interpretation; Fitzgerald, F. Scott, -- 1896-1940 -- Criticism; Authors, American; American authors